2016
DOI: 10.1136/jclinpath-2015-203585
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of immunohistochemical biomarkers that differentiate chromophobe renal cell carcinoma from renal oncocytoma

Abstract: We recommend a panel of IHC biomarkers of amylase α1A, Wnt-5a, FXYD2, ARPP, CD63, TGFβ1, CK7, S100A1, caveolin-1 and claudin-7 to aid in the differentiation of chRCC and RO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 56 publications
7
39
0
Order By: Relevance
“…Altogether, accumulating evidences consistently support that CAV1 plays an important role in cancer progression – the specific nature of which seems to depend on several factors, including cancer type and stage, lesions on CAV1 or its associated genes, its protein expression level and subcellular localisation. The fact that CAV1 could serve as a clinical biomarker [45, 46] further emphasizes its importance in cancer. However, despite knowledge of its expression pattern and roles in different cancers, it is still unclear whether CAV1 expression is a property that accompanies or directly drives altered metabolism, or if changes in energy balance modulate CAV1 level towards or against cancer progression.…”
Section: Relevance Of Caveolin-1 In Cancermentioning
confidence: 99%
“…Altogether, accumulating evidences consistently support that CAV1 plays an important role in cancer progression – the specific nature of which seems to depend on several factors, including cancer type and stage, lesions on CAV1 or its associated genes, its protein expression level and subcellular localisation. The fact that CAV1 could serve as a clinical biomarker [45, 46] further emphasizes its importance in cancer. However, despite knowledge of its expression pattern and roles in different cancers, it is still unclear whether CAV1 expression is a property that accompanies or directly drives altered metabolism, or if changes in energy balance modulate CAV1 level towards or against cancer progression.…”
Section: Relevance Of Caveolin-1 In Cancermentioning
confidence: 99%
“…Although several existing prognostic systems and models have been established with considerable prognostic ability, they still need to be improved. In recent years, there has been a growing interest in identifying novel tumor markers not only for diagnostic purposes but also to improve the prediction of prognosis 3,4. Combining the molecular biomarkers with conventional models might provide more individualized diagnosis and treatment based on molecular characteristics of the tumor 57…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the CK7 IHC study provided similar results as revealed by our meta-analysis where CK7 has been identified as the most studied IHC biomarker in the differentiation between chRCC and RO (Ng et al 2016). From this meta-analysis, we also recommended CK7 as part of our panel of IHC biomarkers than can be useful in differentiating chRCC from RO.…”
Section: Cytokeratinsupporting
confidence: 72%
“…Therefore, a metaanalysis was conducted to answer this question. This meta-analysis has been published (Ng et al 2016) (Appendix 6).…”
Section: Meta-analysis Of Immunohistochemical Biomarkers That Differementioning
confidence: 99%
See 1 more Smart Citation